Speech Task Force and Quality of Life after Surgery in Children with Cleft Lip and Palate: Limitation of Professionals - Prathanee, Benjamas; Thanawirattananit, Panida; Surit, Phrutthinun; Mitkitti, Ratchanee; Makarabhirom, Kalyanee (Archives of Plastic Surgery, 2024)
Background Shortage of speech and language therapists results in lack of speech services. The aims of this study were to find the effectiveness of a combination speech therapy model at Level IV: General speech and language pathologist (GSLP) and Level V: Specific speech and language pathologist (SSLP) in reduction of the number of articulation errors and promotion the quality of life (QoL) for children with cleft palate with or without cleft lip (CP ± L).Methods Fifteen children with CP ± L, aged 4 years 1 month to 10 years 9 months (median = 76 months; minimum:maximum = 49:129 months) were enrolled in this study. Pre- and post-assessment included oral peripheral examination; articulation tests via Articulation Screening Test, Thai Universal Parameters of Speech Outcomes for People with Cleft Palate, Hearing Evaluation, The World Health Organization Quality of Life Brief_Thai (WHOQOL-BRIEF-THAI) version questionnaire for QoL were performed. Speech therapy included a 3-day intensive speech camp by SSLP, five 30-minute speech therapy sessions by a GSLP, and five 1-day follow-up speech camps by SSLP that provided four 45-minute speech therapy sessions for each child.Results Post-articulation revealed statistically significant reduction of the numbers of articulation errors at word, sentence, and screening levels (median difference [MD] = 3, 95% confidence interval [CI] = 2–5; MD = 6, 95% CI = 4.5–8; MD = 2.25, 95% CI = 1.5–3, respectively) and improvement of QoL.Conclusion A speech task force consisting of a combination of Level IV: GSLP and Level V: SSLP could significantly reduce the number of articulation errors and promote QoL.
Keywords: speech task force; quality of life; speech therapy; limited resources; lack professional